Inquiry Into Urban Adolescent Independent Reading Habits: Can Gee's Theory of Discourses Provide Insight? - Knoester, Matthew (Journal of adolescent & adult literacy, 2009)
Students must be welcomed into the dominant Discourses valued in schools and given opportunities to succeed, as each step from a more comfortable primary Discourse may be risking rejection and failure for them.